The First Ex-Situ Germination and Dispersal Mechanisms of the Rare, Critically Endangered Tree, Pleodendron costaricense. (19th May 2022) - Pillco Huarcaya, Ruthmery; López Morales, Marvin; Álvarez-Alcázar, Leonardo; Whitworth, Andrew
Background and Research aims: The extinction of relict and rare tree species is accelerated by habitat loss and climate change. Pleodendron costaricense is a critically endangered tree, with only four mature individuals known in Southern Pacific Costa Rica. With the discovery of three additional trees, we set out to learn more about P. costaricense's natural history and attempt the first successful germination. Methods: We collected fruits from two trees and carried out preliminary germination trials in a nursery at the study site. We also used camera traps in one of the fruiting mother-trees to understand natural dispersal mechanisms of the species. Results: Although plagued by excessive levels of invertebrate predation, we were able to germinate and produce 59 saplings ready for restoration planting. Five mammal species were detected on the camera traps feeding on the fruits, along with one primate potentially using the fruits as a topical medicine. Conclusion: P. costaricense can be propagated ex-situ, potentially with greater success using stimulating hormones. To improve production rates, future efforts should focus on the protection of germinating seeds and saplings from seed predators. We also identified numerous potential natural mammalian seed dispersers, mostly in the family Procyonidae. Implications for Conservation: Given the propagation knowledge we have developed, the active restoration efforts of the saplings by Osa Conservation to help increase population numbers, and the strict protection of the two fruiting mother trees, there is now the possibility to attain a positive conservation outcome for this critically endangered species.